Pendekatan Asset-Based Community Development dalam Pengabdian Masyarakat: Studi Kasus Pendirian Gugus Depan Pramuka IAI Badrus Sholeh - Ramadina, Indah Nur; Muhammad, Alfet Robi Nur (MAYARA: Jurnal Pengabdian Masyarakat, 2025)
The purpose of this community service project was to establish a scout troop in accordance with the values of Islamic boarding schools at IAI Badrus Sholeh. The scout troop was established using an Asset-Based Community Development approach. The result of the community service activity is the establishment of a scout troop using the ABCD approach, which includes the discovery stage, where IAI Badrus Sholeh has potential assets that support the establishment of a scout troop. The dream stage, where the enabler formulates the target to be achieved, which is to establish a scout troop in accordance with Islamic boarding school values. The design stage involved discussions on the types of assets that could be used to ensure the successful establishment of the scout troop. The definition stage involved discussions to determine the details of the implementation of the establishment of the scout troop. In the implementation stage, the empowerment team sent a letter requesting a scout troop number to the Purwoasri Subdistrict Scout Headquarters and obtained the scout troop number approval document.